Identifikasi Eschericia coli pada Minuman Es Kelapa Muda dengan Metode Most Probable Number (MPN) di Kecamatan Banjarmasin Utara - Hajrah Hidriya; Siti Saidah; Faridah Ariyani (HB PRESS, 2021)
Young coconut ice drink is a type of traditional drink containing good nutrition for the growth of microorganisms such as bacteria. One of the causes of young coconut ice contamination is Escherichia coli. Escherichia coli is a gram-negative bacterium and is a factor causing disease, especially diarrhea. This study aimed to determine the identification of young coconut ice drink with the most probable number (MPN) method. The examination used the MPN method in three stages. The initial test used lactose broth as a fertilizer. If the result was positive, it continued to EC Broth media as a confirmation test. If the result in EC Broth media was positive, it continued to EMB media for the perfection test. The results of the study using nine samples of young coconut ice showed that six samples were positively contaminated by E.coli (67%) and three samples were not contaminated by E.coli (33%). Based on the results of the study, it could be concluded that young coconut ice drinks sold in the North Banjarmasin Subdistrict were mostly contaminated with E.coli bacteria that were declared not to meet the standard requirements for food/beverage sales according to the Food and Drug Supervisory Agency (BPOM ISBN 978-602-3665-11-26) in 2012.